The neuroprotective effects of progesterone on traumatic brain injury: current status and future prospects - Wei Jing; Xiao Guo-min (Acta Pharmacologica Sinica; Vol 34, No 12 (December 2013): Acta Pharmacologica Sinica, 2016)
Traumatic brain injury is the leading cause of morbidity and mortality in young adults. The secondary injury in traumatic brain injury consists of a complex cascade of processes that simultaneously react to the primary injury to the brain. This cascade has been the target of numerous therapeutic agents investigated over the last 30 years, but no neuroprotective treatment option is currently available that improve neurological outcome after traumatic brain injury. Progesterone has long been considered merely a female reproductive hormone. Numerous studies, however, show that progesterone has substantial pleiotropic properties as a neuroprotective agent in both animal models and humans. Here, we review the increasing evidence that progesterone can act as a neuroprotective agent to treat traumatic brain injury and the mechanisms underlying these effects. Additionally, we discuss the current progress of clinical studies on the application of progesterone in the treatment of traumatic brain injuries.